Hemosiderin deposition in the brain as footprint of high-altitude cerebral edema - Schommer, Kai; Kallenberg, Kai; Lutz, Kira; Bärtsch, Peter; Knauth, Michael (Neurology, 2013)
Objective: Based on recent findings of microhemorrhages (MHs) in the corpus callosum (CC) in 3 individuals after nonfatal high-altitude cerebral edema (HACE), we hypothesized that hemosiderin depositions in the brain after high-altitude exposure are specific for HACE and remain detectable over many years. - Methods: This was a cross-sectional study involving 37 mountaineers in 4 groups: 10 had experienced HACE, 8 high-altitude pulmonary edema, 11 severe acute mountain sickness, and 8 had climbed to altitudes ≥6,962 m without developing any high-altitude illness. HACE was defined as ataxia necessitating assistance with walking and/or decreased consciousness. Within <1 to 38 months after the qualifying incident, MRI of the brain was performed using a 3-tesla scanner and high-resolution susceptibility-weighted magnetic resonance sequences for detection of hemosiderin depositions, which were quantified by a score. - Results: Unequivocal MHs located in the splenium of the CC were found in 8 subjects and questionable MHs were found in 2 subjects 1 to 35 months after HACE. They were located outside the CC in 5 more severe cases. MHs remained unchanged in those reexamined after 12 to 50 months. A few unequivocal MHs in the splenium of the CC were found in one subject after severe acute mountain sickness, while one subject with high-altitude pulmonary edema and 2 of the extreme altitude climbers had questionable lesions. In all other subjects, MHs were unequivocally absent. - Conclusions: MHs detectable by susceptibility-weighted MRI predominantly in the splenium of the CC are long-lasting footprints of HACE.
Gesehen am 15.07.2021